1997
DOI: 10.1016/s0014-5793(97)00275-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative processing of bovine leukemia virus envelope glycoprotein gp72 by subtilisin/kexin‐like mammalian convertases

Abstract: Intracellular proteolytic processing of bovine leukemia virus (BLV) envelope glycoprotein precursor (gp72) at the Cterminal end of the RVRR 268 J, site is an essential step for virus infectivity. Subtilisin/kexin-like convertases cleave proproteins at preferred RX(K/R)R J, sites, including those commonly found in viral envelope glycoprotein precursors. We first demonstrated that gp72 is processed into gp51/gp30 in both CV1 cells and the furin-deficient LoVo cells, leading us to compare the ability of mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…As expected, neither of the well-characterized furin-deficient cell lines, LoVo or RPE.40, processed soluble ⌬MT1-MMP to its mature form. LoVo cells have been reported to express PACE4 as well as PC7, and this furin-deficient cell line can process other RXKRencrypted targets including human immunodeficiency virus-1, E-cadherin and gp-160 (Gu et al, 1995;Decroly et al, 1997;Zarkik et al, 1997;Posthaus et al, 1998). However, neither PACE4 nor PC7 appeared to play a major role in the processing of ⌬MT1-MMP in LoVo cells.…”
Section: Proprotein Convertases As Processing Enzymes For Mt1-mmpmentioning
confidence: 95%
See 1 more Smart Citation
“…As expected, neither of the well-characterized furin-deficient cell lines, LoVo or RPE.40, processed soluble ⌬MT1-MMP to its mature form. LoVo cells have been reported to express PACE4 as well as PC7, and this furin-deficient cell line can process other RXKRencrypted targets including human immunodeficiency virus-1, E-cadherin and gp-160 (Gu et al, 1995;Decroly et al, 1997;Zarkik et al, 1997;Posthaus et al, 1998). However, neither PACE4 nor PC7 appeared to play a major role in the processing of ⌬MT1-MMP in LoVo cells.…”
Section: Proprotein Convertases As Processing Enzymes For Mt1-mmpmentioning
confidence: 95%
“…However, in contrast to LoVo cells, RPE.40 cells do express PC6 (as both the transmembrane-anchored and soluble forms, PC6B and P6CA, respectively; Duguay et al, 1997). Interestingly, PC6, like furin, can process RXKR-, RXXR-, and KXXR-containing molecules (Zarkik et al, 1997;Cui et al, 1998). Furthermore, because PC6 cannot be de-tected in LoVo cells (Vollenweider et al, 1996;Logeat et al, 1998), differences in the MT1-MMP processing pathways displayed between LoVo and RPE.40 cells are likely attributed to each cell line's distinct repertoire of processing enzymes.…”
Section: Proprotein Convertases As Processing Enzymes For Mt1-mmpmentioning
confidence: 99%
“…It also behaves as a suicide substrate inhibitor, as binding to the active site results in an equal probability that proteolysis will ensue or that a kinetically trapped SDS-stable complex with the enzyme will be formed (Dufour et al 1998. Because of its high selectivity toward SPC1 , this novel inhibitor has already been used to assess the biological role of SPC1 in processing different precursors , Denault et al 1995b, Watanabe et al 1995, Decroly et al 1996, Kayo et al 1997, Zarkik et al 1997, Abrami et al 1998, Cui et al 1998, Logeat et al 1998. Other naturally occuring substances have been tested for their ability to inhibit SPCs.…”
Section: Spc Inhibitionmentioning
confidence: 99%
“…The separation was monitored on-line by both UV absorbance at 210 nm and fluorescence (λ ex l 320 nm and λ em l 420 nm), measured in arbitrary units. The various peaks with retention times shown in parenthesis were analysed by amino acid composition and MALDI-TOF-MS. Abbreviations : NT 1 , fluorescent N-terminal fragment (1-13) generated by cleavage at the physiological site (heavy arrow) ; NT 2 , fragment (1-9) generated by cleavage at an alternate site (thin arrow) ; CT 1 and CT 2 , non-fluorescent C-terminal fragments (14)(15)(16)(17) and (10)(11)(12)(13)(14)(15)(16)(17) repectively.…”
Section: Figure 1 Rp-hplc Chromatograms Showing the Separation Of Digmentioning
confidence: 99%
“…Thus it has been demonstrated that conditions favouring viral replication cause a significant upregulation of candidate processing enzymes such as furin and PC7 [14][15][16][17][18]. These and other studies have indicated that furin and PC7 are the major candidate surface glycoprotein (including HIV gp160) convertases in lymphocytes [15][16][17][18]. This finding inspired various groups to examine the possible participation of PCs in other viral and opportunistic infections [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%